Narcissistic Leaders–Promise or Peril? The Patterns of Narcissistic Leaders’ Behaviors and Their Relation to Team Performance - Schmid, Ellen A.; Knipfer, Kristin; Peus, Claudia V. (Frontiers in Psychology, 2021)
Although leader narcissism has attracted substantial attention in organizational science and practice, the relationship between leader narcissism and performance remains somewhat opaque and elusive. Our first aim was to explore how leader narcissism leverages performance in an environment that is conducive to narcissism: entrepreneurship. Concretely, we hypothesized that moderate leader narcissism is beneficial for entrepreneurial team performance. Second, we aimed to better understand this relationship by taking a closer look at the leadership behaviors that are associated with different levels of narcissism. We conducted a two-study field investigation using multiple sources and combining quantitative and qualitative methods. In a quantitative field study, we found a curvilinear relationship between team perceptions of leader narcissism and team performance as rated by entrepreneurship experts. A qualitative follow-up interview study revealed that narcissistic leaders show functional and destructive behaviors, but the exact patterns of behaviors determined if narcissistic leaders led their teams to success or not. This research contributes to research at the intersection of business and psychology by providing a nuanced view of the effect of narcissism on performance that goes beyond the current ‘good versus bad’–perspective.